Circulating chemerin levels are determined through circulating platelet counts in nondiabetic Taiwanese people: A bidirectional Mendelian randomization study. (March 2021) - Hsu, Lung-An; Chou, Hsin-Hua; Teng, Ming-Sheng; Wu, Semon; Ko, Yu-Lin
Abstract: Background and aims: Platelet count (PLT) is a predictor of metabolic and inflammation-related disorders. Platelets can release prochemerin, which acts as a link between coagulation and inflammation and between innate and adaptive immunity. The causal effect between PLT and circulating chemerin level has not been elucidated. Methods: Nondiabetic participants with samples in the Taiwan Biobank were recruited for a genome-wide association study (GWAS) based on PLT (17, 037 participants) and chemerin levels (3887 participants). A bidirectional Mendelian randomization (MR) study was conducted to determine the association between circulating PLT and chemerin levels. Results: For a GWAS of PLT, 11 gene loci were found to have genome-wide significance. For a GWAS of chemerin levels, two gene loci, RARRES2 and HLADQA2-HLADQB1, were found to have genome-wide significance. Age, sex, body mass index, leukocyte count, hemoglobin, mean blood pressure, hemoglobin A1C, serum total bilirubin, aspartate aminotransferase, triglyceride, and low-density-lipoprotein cholesterol levels, estimated glomerular filtration rate, and circulating chemerin level were found to be independently associated with PLT through a stepwise regression analysis. A bidirectional MR study revealed weighted genetic risk scores (WGRSs) for PLT were significantly associated with chemerin levels by using a two-stage least-square method in a multivariate analysis ( p  = 0.0031), and no significant association between chemerin level WGRSs and PLT was noted. Sensitivity analysis further revealed no violation of the exclusion-restriction assumption with PLT-determining genotypes on chemerin levels. Conclusions: Through a bidirectional MR analysis, our data revealed that chemerin levels were determined based on circulating PLT. Circulating chemerin levels can be intermediates between PLT and future metabolic and inflammation-related disorders. Graphical abstract: Image 1 Highlights: Both platelet and chemerin play a role in the pathogenesis and prognosis of metabolic and inflammation-related disorders. High platelet count is associated with high circulating chemerin levels. Mendelian randomization revealed that chemerin levels were determined based on circulating platelet. Circulating chemerin levels can be intermediates between platelet and future metabolic and inflammation-related disorders.